An Analysis of Qualitative Open Defecation Behavior of North Maluku Province in 2017 (A Case Study at Community of Toseho Village in Archipelago Tidore City) - Norma B Toduho; Bambang Setiaji; Ratu Ayu Dewi Sartika (JUMP Health (Journal of Ultimate Public Health), 2019)
Background : Public Health Development Index in 2013, the correct behavior of defecation in North Maluku is about 0.78 percent and the rest still have Open Defecation Behavior.Purpose : The purpose of this research is to find out the Open Defecation Behavior (Case Study at Community of Toseho Village in Tidore Kepulauan City) in North Maluku Province.Methods : The methods used are observation, in-depth interview, and FGD (Focus Group Discussion). Determinant of informants used "purposive sampling" method.Results :  The results of the study found lack of family, public figure, and public religious about  perceptions against open defecation and latrine availability due to difficult geographic location (coastal), absence of latrines either private or public latrines (damaged), limited finances, and ashamed of using neighbor latrines. There is not ‘toilet social gathering’ established by health workers and public figure. Open defecation behavior habits in the community stays since the past until now and on every age, whereas the majority of the people are muslim. Open defecation places (adults and small children) are at beachside, back of the house (mangrove forest), side of the house, and at terrace. There are not regulation from public figure or public religious against the community who does open defecation. public figure and public religious never invite the community by inculcating islamic value that is maintainingpersonal hygiene and environment and sanitation as part of the faith. Other than that one of the public figure even provide an example that is not good, where the public figure had served as chairman of the Neighborhood Association, even do open the faction, so that his bihavior in samples by the citizens themselves.Suggestion : It is expected that health workers will be more optimal in carrying out community empowerment activities through family-related approaches to sanitation and Clean and Healthy Life Behavior, public figure and publich religious conducting activities that instill Islamic values to the community to maintain sanitation and clean and healthy life behavior.